DO THE DISTRIBUTION OF ZAKAT AND ISLAMIC BANK FINANCING AFFECT INCOME INEQUALITY IN INDONESIA? - Al Haq Kamal; Ratih Purbowisanti; Ageng Asmara Sani; Kusumaningdyah Retno Setiorini (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2021)
This study aims to reveal empirically the extent to which Islamic economics contributes to Indonesia's economic equality. This study uses zakat distribution indicators and financing of Islamic banks as an instrument of income distribution in Islamic economics; GINI coefficients are indicators for measuring income inequality and using panel data with a cross-section of 12 provinces in Indonesia the 2011-2016 period. This study found that the distribution of zakat has a negative effect on income inequality and Islamic bank financing has a positive effect on income inequality.